(untitled) (The Review of Diabetic Studies, 2024)
Background: Central line-associated bloodstream infections (CLABSI) are a leading cause of morbidity and mortality in intensive care units (ICUs). Despite the implementation of evidence-based guidelines to prevent these infections, adherence to these protocols remains inconsistent among ICU nurses, particularly in Saudi Arabia. Previous studies have shown that ICU nurses possess a moderate to high level of knowledge regarding CLABSI prevention but often fail to translate this knowledge into practice. The barriers to adherence include inadequate training, workload pressures, and insufficient institutional support. Aim: This systematic review aims to assess ICU nurses’ knowledge, attitudes, and adherence to evidence- based guidelines for preventing CLABSI in Saudi Arabia, identify barriers to compliance, and propose strategies for improvement. Method: A systematic search was conducted using multiple databases, including PubMed, Scopus, and Google Scholar, to identify studies published between 2021 and 2024. The studies included were cross- sectional or observational in design, focusing on ICU nurses’ knowledge and adherence to CLABSI prevention guidelines. A total of 10 studies were included in the review, and data were synthesized to evaluate the current state of practice. Results: The findings indicate that while ICU nurses in Saudi Arabia have a moderate to high level of knowledge about CLABSI prevention, their adherence to guidelines is suboptimal. Barriers to adherence include time constraints, heavy workloads, and a lack of ongoing training and institutional support. Educational interventions were found to improve knowledge and adherence. Conclusion: Improving adherence to CLABSI prevention guidelines requires ongoing training, institutional support, and regular audits. Addressing the barriers to practice will enhance patient safety and reduce CLABSI rates in Saudi ICUs.